Format Acara Dakwah Efektif di Radio dan TV - Erwan Efendi; Fadia Siregar; Khairul Damanik (Journal on Education, 2023)
This article discusses the effectiveness of Islamic da'wah through radio and television media. Radio and television as one of the audiovisual media are very influential and effective in spreading Islamic da'wah in modern society like today. Effective because it can reach the public at large, messages through radio and television that are presented audio-visually provide information faster than other media and the cultural effects of radio and television are greater than the effects produced by other types of media. Therefore, it can facilitate the delivery of the message of his da'wah. Radio and television media as media builders, develop ideas, and shape people's behavior if the radio and television programs are more moral, radio and television programs must be designed in such a way so as not to go out of the corridors of Islam so that Muslims make radio and television as a medium of da'wah.